Silicon-iron modified biochar remediates cadmium and arsenic co-contaminated paddy soil by regulating cadmium and arsenic speciation - Chen, Yao; Tian, Xin; Wang, Jia-hao; Zhang, Yu; Wang, Jie; Li, Zhang-tao; Zhao, Ke-li; Wu, Ji-zi (Frontiers in Microbiology, 2025)
IntroductionSilicon–iron-modified biochars (SMBCs) were produced to remediate paddy soil contaminated with both cadmium (Cd) and arsenic (As). This study explored the effects of SMBCs on the transformation of Cd and As species in soil and the associated responses of functional genes to elucidate the remediation mechanisms.MethodThree silicon–iron modified biochars were utilized. (i) Silicon dioxide magnetic biochar (SMBC1), (ii) Calcium silicate magnetic biochar (SMBC2), and (iii) Sodium silicate magnetic biochar (SMBC3) were applied to paddy soil.Results and discussionSMBCs increased the soil pH and the concentration of dissolved organic carbon (DOC) by 0.42–0.54 units and 6.6–16.39%, respectively. SMBC treatments reduced the bioavailable concentrations of Cd and As by 29.09–73.63% and 1.67–8.37%, respectively, transforming As(III) into less toxic As(V) and stabilizing soluble Cd into a more inert residual form. Compared to the control, SMBC significantly increased residual Cd concentrations by 2.94–16.17% (p < 0.05) and As(V) concentrations by 11.42–26.07% (p < 0.05). Adding calcium silicate (CaSiO3) at a mass ratio of 5% to magnetic biochar resulted in a residual Cd concentration of 0.79 mg·kg−1 (an increase of 16.86%) and an As(V) concentration of 37.89 mg·kg−1. SMBCs enhanced soil porosity, microbial aioA genes, and sulfate-reducing bacteria, facilitating the oxidation of As(III). Magnetic biochar amended with 5% (CaSiO3) (SMBC2) demonstrated superior efficacy in addressing the co-contamination of Cd and As. The remediation mechanisms include the following: (i) an increase in soil pH and a decrease in dissolved organic carbon (DOC), (ii) enhanced aioA gene activity, promoting the oxidation of As(III) to As(V), and increased dissimilatory sulfite reductase beta subunit (DsrB) gene activity, facilitating the reduction of sulfate ion (SO42−) to sulfide ion (S2−), leading to the formation of cadmium sulfide (CdS) precipitates and additional precipitation involving As and Fe. These results highlight the potential of calcium silicate–modified magnetic biochar as an effective additive for Cd and As co-contaminated soils, providing insights into heavy metals’ stabilization and transformation mechanisms.